2016
DOI: 10.1016/j.jmii.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus suppresses atopic dermatitis-associated cytokines and chemokines in monocytes

Abstract: Tacrolimus suppressed LPS-induced MDC, I-309, IP-10, GRO-α, and TNF-α expressions in monocytes through the MAPK-ERK pathway; thus, tacrolimus may yield therapeutic efficacy by modulating AD-associated cytokines and chemokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…D). We also investigated the production of several inflammatory mediators known to be present in AD lesions [IL‐1β , chemokine motif ligand 1 (CXCL1) , CXCL9 , and EPX ] and observed that they were all significantly reduced following IVM or BMV treatment (Fig. D).…”
Section: Resultsmentioning
confidence: 99%
“…D). We also investigated the production of several inflammatory mediators known to be present in AD lesions [IL‐1β , chemokine motif ligand 1 (CXCL1) , CXCL9 , and EPX ] and observed that they were all significantly reduced following IVM or BMV treatment (Fig. D).…”
Section: Resultsmentioning
confidence: 99%
“…These data are in contradiction with the findings reported by Chang et al . who described an inhibitory effect of tacrolimus on p-ERK but not on p38MAPK phosphorylation [ 26 ]. However, in contrast to the present study in which primary monocytes were investigated, the experiments by Chang et al .…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of studies on the effect of tacrolimus on monocyte functions have been mostly performed in animal models, immortalized cell lines and cord blood cells. These studies report that tacrolimus can suppress the production of IL-1β, IL-10 and TNF-α by polyclonally activated monocytes [ 26 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of these drugs on alloreactive T-cell function have been extensively characterized, but the knowledge of their effect on monocytes is limited [5]. The few in vitro studies that have been conducted in this respect have indicated that TAC and MPA affect cytokine production by monocytes [28,29]. Furthermore, TAC did not affect phagocytosis or production of IL-1β in vitro, whereas MPA did reduce the production of IL-1β [30].…”
Section: A C C E P T E Dmentioning
confidence: 99%